The courtier and the heretic : Leibniz, Spinoza, and the fate of God in the modern world - Stewart, Matthew, 1963- (New York, W.W Norton and Company, 2006)
Philosophy in the late seventeenth century was a dangerous business. No careerist could afford to side with the reclusive philosopher and "atheist Jew" Spinoza. Yet the ambitious young genius Leibniz became obsessed with Spinoza's writings, wrote him clandestine letters, and ultimately called on Spinoza in person at his home in The Hague. Both men were at the center of the intense religious, political, and personal battles that gave birth to the modern age. One was a hermit with many friends; the other, a socialite no one trusted. One believed in a God whom almost nobody thought divine; the other defended a God in whom he probably did not believe. They would come to represent radically different approaches to the challenges of the modern era. In this philosophical romance of attraction and repulsion, greed and virtue, religion and heresy, Matthew Stewart dramatizes a contest of ideas that continues today.--From publisher description
The Hague, November 1676 -- Bento -- Gottfried -- A life of the mind -- God's attorney -- The hero of the people -- The many face of Leibniz -- Friends of friends -- Leibniz in love -- A secret philosophy of the whole of things -- Approaching Spinoza -- Point of contact -- Surviving Spinoza -- The antidote of Spinozism -- The haunting -- The return of the repressed -- Leibniz's end -- Aftermath
Includes bibliographical references (pages 332-339) and index
Keywords: Leibniz, Gottfried Wilhelm, -- Freiherr von, -- 1646-1716.; Spinoza, Benedictus de, -- 1632-1677.; God -- History of doctrines; Nonfiction